Analysis of the National Strategic Program in the Development of Toll Roads in Section Harbor Road II, North Jakarta: The Perspective of State Control Rights - Chamidah, Umi; Roestamy, Martin (DE'RECHTSSTAAT, 2025)
This research aims to analyze the role of the National Strategic Program in the development of toll roads in Section Harbour Road II, North Jakarta, focusing on the perspective of state sovereignty over land. The development of toll roads is crucial for enhancing urban connectivity and mobility. However, it raises concerns regarding national sovereignty over land and resources. Through comprehensive analysis, this research examines the implications of the National Strategic Program on state land sovereignty in the context of toll road development. The study also explores the legal framework, socio-economic impacts, and environmental considerations related to toll road projects. Furthermore, it explores strategies to mediate infrastructure development with the protection of national sovereignty and the rights of affected communities. The findings of this research provide insights for policymakers, stakeholders, and the public to navigate the complexities of toll road development within the framework of national strategic planning and state sovereignty.